Are Malaysian Youths Overdependent on the Internet?: A Narrative Review - Nik Jaafar, Nik Ruzyanei; Bahar, Norharlina; Ibrahim, Normala; Baharudin, Azlin; Wan Ismail, Wan Salwina; Sim, Su Tein; Abdul Aziz, Melisa; Tan, Kit-Aun (Frontiers in Psychiatry, 2021)
Overdependence on the internet is a grave concern that has enveloped Malaysian youths which could lead to a variety of sequelae. This narrative review aims to determine the definition of internet overdependence and its associated factors, as well as the potential preventive and treatment strategies for internet overdependence. From the literature, internet overdependence is regarded as a 3-factor model encompassing salience, self-control failure, and serious consequences. Sociodemographic factors such as age, gender, and ethnicity, as well as psychosocial factors such as depression, anxiety, stress, and loneliness, were found to be associated with internet overdependence among Malaysian youths. A multimodal treatment approach is recommended by the implementation of various types of treatments, integrating disciplines such as pharmacology, psychotherapy, and family counseling. Despite various terminologies being used and unclear conceptualization of its nomenclature, overdependence on the internet is prevalent among youths in Malaysia. Future research should go toward establishing a clear definition of its terminology and attaining more robust evidence on treatment strategies.